Evaluasi Pelaksanaan Program Desa Tangguh Bencana Di Kabupaten Kendal Tahun 2016 - Munir, Miftakhul; Harsasto, Priyatno; Taufiq, Achmad (Journal of Politic and Government Studies, 2017)
Disaster tough village is of village that have own capability toÂ adapted andÂ facing disaster potential threat, andÂ healing soon from disaster impact. Board of Disaster Manajemen District of Kendal (Badan Penanggulangan Bencana Daerah Kabupaten Kendal or BPBD) its a branch of government that have responbility to countermeasures the disaster. I of to decrease disaster risk, BPBD Kendal district there have step before disaster with continue to doing program disaster tough village with society involve to the man actor. In 2016 Kendal district that have 3 disaster tough village in diference of kind disaster.This research used metodic of descriptive qualitative used collective data teknik through interview, observation, and document. The informan in this research is people that knowen well about this field aplication program development.This research, researcher using theory of Thomas Dye â€œevalution of policy its a objective, investigation, systematic and empiris to policy and public program target from the purposeâ€. On the basic from this theory, the implementation disaster tough village program in Kendal district thats couldnâ€™t doing well, because limited facility and thereâ€™s no good kaderisasion program of volunter, and lack of awareness from young generation, thereâ€™s no budgeting to operasional and thereâ€™s no facility to on decrease risk disaster effort, and also theres no participation yet from branch of government in Kendal district to decrease risk disaster effort in Kendal district.Based on reseacrh result, we can the conclusion that the implementation program disaster tough village in Kendal district 2016 still have the of stacles to get purpose. To the next time development disaster tough village program can increase quality and quantity, increase the amount of volunteers, and also have facility support budgeting well.Key word : Disaster Tough Village, Disaster Risk Reduction, and Disaster Management